Preface of the 14th EASN International Conference on “Innovation in Aviation & Space Towards Sustainability Today & Tomorrow” (EASN 2024) - Spiros Pantelakis; Andreas Strohmayer; Nikolaos Michailidis (Engineering Proceedings)
The 14th EASN International Conference on “Innovation in Aviation and Space towards sustainability today & tomorrow” was successfully held in the Concert Hall of Thessaloniki, Greece, from 8 to 11 October 2024 [...]